Diagnosing direct-drive, shock-heated, and compressed plastic planar foils with noncollective spectrally resolved x-ray scattering - Sawada, H; Regan, S; Meyerhofer, D; Igumenshchev, I; Goncharov, V; Boehly, T; Epstein, R; Sangster, T; Smalyuk, V; Yaakobi, B; Gregori, G; Glenzer, S; et al. (2007)
The electron temperature (Te) and average ionization (Z) of nearly Fermi-degenerate, direct-drive, shock-heated, and compressed plastic planar foils were investigated using noncollective spectrally resolved x-ray scattering on the OMEGA Laser System [T. R. Boehly, Opt. Commun. 133, 495 (1997)]. Plastic (CH) and Br-doped CH foils were driven with six beams, having an overlapped intensity of ∼1× 1014 W cm2 and generating ∼15 Mbar pressure in the foil. The plasma conditions of the foil predicted with a one-dimensional (1-D) hydrodynamics code are Te ∼10 eV, Z∼1, mass density ρ ∼4 g cm3, and electron density ne ∼3× 1023 cm-3. The uniformly compressed portion of the target was probed with 9.0-keV x rays from a Zn Heα backlighter created with 18 additional tightly focused beams. The x rays scattered at either 90° or 120° were dispersed with a Bragg crystal spectrometer and recorded with an x-ray framing camera. An examination of the scattered x-ray spectra reveals that an upper limit of Z∼2 and Te =20 eV are inferred from the spectral line shapes of the elastic Rayleigh and inelastic Compton components. Low average ionizations (i.e., Z<2) cannot be accurately diagnosed in this experiment due to the difficulties in distinguishing delocalized valence and free electrons. Trace amounts of Br in the CH foil (i.e., 2% atomic concentration) are shown to increase the sensitivity of the noncollective, spectrally resolved x-ray scattering to changes in the average ionization. The experimentally inferred electron temperatures are comparable to the 1-D predictions. © 2007 American Institute of Physics.